Analisis Faktor-Faktor yang Mempengaruhi Persepsi Wakif Wakaf Uang di Jember - Lilis Yuliati; Ayuninda Rochmaningsih; Lusiana Ulfa Hardinawati (Institut Agama Islam Negeri Ponorogo, 2023)
The current potential of cash waqf can be a solution to education problems in Indonesia. with the collection of cash waqf it can provide new hope for people who are unable to take education up to college. The purpose of this research is to look at the factors that influence the perception of waqf of cash waqf, especially in Jember Regency. This research uses descriptive quantitative research methods with logistic regression analysis tools, the intended factors include four variables namely education, understanding of waqf, religiosty, and access to media and information. Based on the results of the reasearch conducted, it found that two variables affect the perception of wakif on cash waqf. The variables that have an effect are the level of understanding of waqf and the religiosity with that significance are 0,035 and 0,023. While the variables of education adn access to media and information get the significance effect get the result 0,367 and 0.948.